PENGUKURAN EFEKTIVITAS IKLAN (STUDI KOMPARASI: IKLAN MEDIA CETAK DAN IKLAN MEDIA ONLINE): Lasmery RM Girsang - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2017)
The shift in advertising in the media have change of strategy in terms of providing for the cost of the ad campaign products/services providers who make the company had to think hard to be able to introduce products / services that attract public attention. Therefore, quantitative research based Theory Usability and Satisfaction (Uses and Gratification Theory) will measure the effectiveness of ads (a comparative study: print ads and online media advertising) by mapping the EPIC model of the 111 respondents in Jakarta. The results were as follows: (1) The average scores for the dimension Empathy magazine ad for 3,74, while on youtube of 3.6; (2) The average scores for the dimensions of Persuasion advertisement in a magazine of 3.60 while on youtube of 3.45; (3) The average scores for the dimensions of the ad in the magazine Impact 3,82 while on youtube by 3, 765; (4) The average scores for the dimensions of a magazine ad Communication of 3.85 while on youtube of 3.84; and (5) EPIC magazine advertising rate of 3.75 while on youtube of 3.67.